Gastrointestinal Physiology A Clinical Approach - Trowers, Eugene. (Springer International Publishing : Imprint: Springer, 2014)
This volume provides a practical hands on guide to gastrointestinal physiology. The book emphasizes an appreciation of basic physiological concepts and their application to novel clinical situations. It exposes the physician-in-training to fundamental principles that are useful in treating patients and lays the groundwork for more advanced study in the future. The authors present relevant cases which incorporate newer adult learning strategies in medical education.  These cases provide a forum in which the student can apply acquired knowledge, skills and attitudes.  Connections are made to reader’s life, whether in the classroom, on the wards or out and about town. Designed for medical students who are studying gastrointestinal physiology for the first time, Gastrointestinal Physiology: A Clinical Approach provides a superb review for upper level medical students and house officers.   Nursing and allied health professions students will also find this text to be a useful guide.  GI fellows and attending physicians in need of a concise review of fundamental GI physiology principles will also benefit from reading this book. .